Analysis of Bolton tooth size discrepancies among the different malocclusion groups in a Filipino sample population - Ying Zhang
The attainment of an optimum occlusal function in orthodontic treatment is based on comprehensive diagnosis and treatment planning. For the best possible outcome, the teeth in both arches must be appropriately sized. Tooth size discrepancies should be detected and considered during initial diagnosis and treatment planning to achieve an excellent result in the finishing stage. The present studies aimed to determine the mean Bolton anterior and over-all tooth size ratios and the percentage of patients having significant tooth-size discrepancies in a Filipino sample population. One hundred and forty-two subjects were divided according to Angle's Class I, II and III malocculsion groups. A TESA Digit-Cal caliper accurate to the nearest 0.01 mm was used to measure the casts. The important conclusions of the present study were as follows: (1) The prevalence of anterior tooth size discrepancies in the Filipino sample was significantly high enough to emphasize the importance of performing the Bolton tooth size analysis prior to orthodontic treatment planning; (2) Mesiodistal tooth sizes, tooth size ratios and prevalence of tooth size discrepancies were established in malocclusion groups for the sample of the present study; (3) There were no statistically significant gender differences for the Bolton tooth ratios and in the prevalence of tooth size discrepancies (+/- 2 SD outside of Botlton's mean) among malocclusion groups. Filipinos generally have larger mesiodistal tooth dimensions in males than females; (4) Significant bilateral differences were found on some of the teeth; (5) No significant differences were found among malocclusion groups for the anterior ratios. A significant difference was observed between Class II and Class III group for the over-all ratios. Not statistically significant differences in the prevalence of tooth size discrepancies among the malocclusion groups; (6) No statistically significant differences were found for the over-all ration in malocclusion group (Dizon's study). For the anterior ratios, Class II and Class III malocclusion groups showed significantly higher values than those of the normal occlusion group. Many teeth showed statistically significant larger mesiodistal tooth dimensions in the malocclusion groups than in the normal occlusion groups except for mandibular first molars; (7) Racial differences for tooth size, tooth size ratios, and the prevalence of intermaxillary tooth size discrepancies were investigated.